Animal models of asthma - AKKOÇ, TUNÇ (My University, 2010)
Allergic disease such as asthma, rhinitis, and eczema are increasing prevelance and affect up to 15% of population in Westernized countries. Among them, asthma is a chronic inflammatory disease of airways and the underlying physiological and immunological processes are not fully understood. Mouse models of asthma dupicates many features of human asthma, including airway hyperreactivity, andairway inflammation. Therefore, relevant models for asthma are important to understand the mechanism of disease and therapeutical approach. In this article, basicly various animal models of asthma and some theraputic approaches are disscussed.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Asthma; Mouse; Ovalbumin; Regulatory cells; REGULATORY T-CELLS; ALLERGIC AIRWAY INFLAMMATION; MURINE MODEL; IMMUNE DYSREGULATION; TOLERANCE INDUCTION; LUNG INFLAMMATION; MOUSE MODELS; FOXP3; INTERLEUKIN-10; IL-10; animal; asthma; model